Aﬀective state recognition through analysis of electroencephalogram signals by using extreme gradient boosting - khan, Md. Sakib; Salsabil, Nishal; Amir, Rayeed; Khandaker, Moumita (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.